Exergetic sustainability and economic analysis of hybrid solar-biomass dryer integrated with copper tubing as heat exchanger. Issue 2 (February 2020) - Ndukwu, M.C.; Simo-Tagne, M.; Abam, F.I.; Onwuka, O.S.; Prince, S.; Bennamoun, L.
Abstract: The aim of this study is to present a new hybrid solar-biomass dryer and carry out thermal analysis based on energy and exergo-sustainability analysis considering all the available exergy stream of solar radiation, air stream through the collector, and exergy of the moisture in the product. The research also presented the environmental impact and economic analysis of using the dryer. Performance evaluations show that at collector efficiency of 20.81%–21.89 %, the developed solar dryers can save between 10 – 21hrs of drying time in drying 5 mm thick plantain slices to 15 % moisture content from initial moisture content of 66 % w.b when compared to drying under the open sun. The improvement potential ranged from 0.036 to 20.6W while the waste exergy ratios and sustainability index ranged from 0.38 - 0.55 and 2.3–6.11 respectively. Application of the solar dryers can save between 44 -3074 of CO2 entering the atmosphere per year while 2.94 to 205.43 could also be saved at 10–100% rate of usage when compared to diesel fired dryer. The total energy consumption for drying ranges between 5.52 and 35.47 MJ, while the specific energy consumption ranged from 4.3 to 26.2 kWh/kg. The exergy efficiency ranges from 5.6 – 95.13 % during the sunshine hours. Abstract : Energy; Agricultural engineering; Environmental analysis; Environmental assessment; Environmental engineering; Environmental impact assessment; Exergy; Energy; Biomass; Plantain; Drying; Hybrid solar dryer